Female Cleric in Raising Health Awareness of Primary School Students at Pesantren An-Nur Ngrukem Bantul - Ichsan, Ahmad Shofiyuddin; Rahmawati, Eka; Akbar, Khilda Ngiliya; Qodriyah, Indah Nor; Sholikah, Marhatun; Fairuzy, Rifda (Al-Azkiya: Jurnal Pendidikan MI/SD, 2025)
This study aimed to investigate the role of female clerics in promoting health awareness among primary school students at the Islamic Boarding School (Pondok Pesantren) An-Nur in Bantul, Yogyakarta. Researchers employed a qualitative method, utilising a case study approach. Researchers collected data through observation, interviews, and documentation. The study results showed that health was important in pesantren. For this reason, the role of women scholars was crucial in mobilisation. The role of women scholars in promoting health awareness among students (santri) at Pesantren An-Nur Bantul included understanding and raising the healthy snacking movement, socialising the importance of maintaining parents' health at home, strengthening boarding school regulations on student health, and creating a healthy canteen for students within the pesantren environment. The impact of this movement could be felt directly by the decrease in the number of students who were sick with cough and stomach acid. The effect was increasingly felt that the healthy canteen also offered low prices on every item, allowing for the implementation of low-budget financial management. It means that the impact of this santri health awareness has been proven, as they have become accustomed to implementing healthy and clean living behaviours in themselves and their environment. For this reason, the role of women scholars in this movement enabled them to maintain the stability of the pesantren climate and raise awareness about the importance of preserving the health of the self, family, and the environment as a whole.